Fungsi dan Peranan Pemangku Adat Rantau Singingi Kabupaten Kuantan Singingi - Raja Amin (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
Overseas Singingi as the former "zelfbestuur van Singingi", a highly respected and recognized by the Indian colonial government as a source of law Belanda.Adat life (living law), and developed in indigenous communities containing the values, norms or rules can bind and be a guide in the daily behavior of public life. Indigenous values are so smooth and coincided with the teachings of Islam ". “adat syarak jointed, jointed syarak kitabullah(Al-Quran)". In the life of society, nation and state, there are three main elements of institutional living and growing in community (indigenous), which each run and side by side, harmonious and balanced, namely Indigenous, Religion and Government, among closely related and can not be separated, as in sinonimkam customary phrase, "Tali Tigo Sapilin", Furnaces --Tigo Sejarangan "The function and position the three elements above, as one element of an institution that live and thrive in the community, which is the regulator of the behavior of citizens . And governance as one of the Agency for help and be a partner with government in the smooth running wheels of government, community and religious development. The function and role of traditional authorities in public life, namely as a main component holder or upstream of the traditional powers itself, which govern the behavior of the rate environment and citizens offspring nephew respectively. As a public figure or "torches Bendang in village, go place to ask and go home where barita.And than as parents and elders in Village and as mandate and problems - children - grandchildren nephew. Related to the function and role of indigenous stakeholders above, local governments need to provide guidance to traditional institutions and traditional authorities in indigenous communities, so that indigenous stakeholders through traditional institutions can play a role and be a partner of the government, especially the village government in governance, development and empowerment of communities, which has been primarily in the New Order government, indigenous existence in the government seriously neglected, even been replaced by the role of the central government's decentralization of states. By turn traditional original values in the form of traditional village through policy formation of the Law on the village.